A comprehensive review on solar cooker tracking techniques for performance enhancement. Issue 1 (February 2021) - Gokul, V; Dhinesh, S; Kalaiyarasu, K; Kalidasan, B; Ravikumar, M
Abstract: The paper provides a review on solar tracking system for solar cooker and its potential in increasing its efficiency. This paper mainly discusses the solar trackers for increasing the work output. This technique assists in increasing the amount of radiation falling on solar cookers. The types of solar tracking based on their degree of freedom are single axis solar tracking system and dual axis solar tracking system and its classification are discussed in this paper. The solar tracker types based on the actuating systems are also discussed. The tracking system suitable for the solar cooking applications is mentioned in this paper.